Solving an equation by iteration
I need to solve an equation for a course for psychology, but since I am studying psychology maths is not really my thing...
The equation I need to solve is:
xt+1 = f(xt) = axt(1-2xt)
The docent provide an example in the lecture (a logistic map equation with iteration, needed for understanding complex dynamic behaviour) but I don't get the steps in between and this is a bit too complex for me :) This was his example:
i=0 Y0->Y1= rY0(1–Y0)
i=1 Y1->Y2= rY1(1–Y1)
= r2Y0= r rY0(1–Y0) (1–rY0(1–Y0) )
Can someone help me (also writing the steps I need to solve the equation)
I would be far mooore than thankful!
A desperate student from the Netherlands :)